PENGARUH PENDAPATAN TERHADAP TABUNGAN PADA MASYARAKAT NELAYAN DI DESA KUALA SECAPAH KECAMATAN MEMPAWAH HILIR - Rahmawati, Nanda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrctThis study aims to determine the effect of income on savings of fishing communities in Kuala Secapah Village Mempawah Hilir District Mempawah, West Kalimantan Province. The research method used is descriptive method with the form of research used is a form of relationship studies (interrelationship Studies). The results showed that there is no influence between independent variables (X) on the dependent variable (Y) based on the results of the questionnaire to the fishing community. Income of fisherman is included in very high category that is 62,2% with frequency 80 responden, but saving society of fisherman is very low because of dominant 98 responden save below 1,500.000 equal to 83,76% .Alternative of fisherman empowerment can be done by reducing dependence on loan shark. And the first step that must be done is the existence of an institution that can replace the role of loan sharks, especially in the provision of borrowing money, either for capital or other purposes. Keywords: Income, Savings, Influence